Between Economy and Security. Dilemmas of Sustainable Development in the Covid-19 Era – an Example of Great Britain - Rydzewski, Paweł (Problemy Ekorozwoju, 2020)
The coronavirus Covid-19 pandemic has disrupted social stability in many countries around the world. This has consequences for sustainable development. In a situation of stability, two competing pillars of sustainable development: the economic and the environmental one, are in the lead – as long as the basic needs of most people are satisfied. In the conditions of instability, the social pillar begins to dominate, pushing the economic and environmental pillars to the background. The fight against the pandemic is or has been carried out in different countries in different ways. We can talk about the Chinese, Taiwanese, or European models, among others. In the United Kingdom, the laissez-faire model was used for a short time. This was an interesting strategy (though a very risky one) that attempted to reconcile different pillars of sustainable development in the face of crisis, seeking a compromise between health considerations, social situation, and the requirements of the economy. However, this approach was quickly rejected under the influence of public opinion, the media and scientific authorities. In the situation of impending crisis, the social pillar began to dominate. The dilemma economy vs. security was resolved according to the hierarchy of needs (with security being a more basic need). This is a tip for the future – for social policy and planning in times of stability. In a situation of deep biological crisis (as opposed to economic crises), the social factor comes to the fore in the end, at the expense of all others. Within the social factor, the hierarchy of goals will be established according to the hierarchy of needs.